2003
DOI: 10.1289/ehp.5717
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mercury in urine as an indicator of exposure to low levels of mercury vapor.

Abstract: We conducted a pooled analysis to investigate the relationship between exposure to elemental mercury in air and resulting urinary mercury levels, specifically at lower air levels relevant for environmental exposures and public health goals (i.e., < 50 microg/m3 down to 1.0 microg/m3). Ten studies reporting paired air and urine mercury data (149 samples total) met criteria for data quality and sufficiency. The log-transformed data set showed a strong correlation between mercury in air and in urine (r = 0.774), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 48 publications
1
17
1
5
Order By: Relevance
“…Urine and serum or plasma THg concentrations are good biomarkers of level of exposure to Hg 0 vapor or divalent Hg (6,9,10). In this study, THg concentration in urine was measured to assess the level of exposure of mine workers to Hg 0 vapor, because urine samples from the mine workers were easy to obtain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urine and serum or plasma THg concentrations are good biomarkers of level of exposure to Hg 0 vapor or divalent Hg (6,9,10). In this study, THg concentration in urine was measured to assess the level of exposure of mine workers to Hg 0 vapor, because urine samples from the mine workers were easy to obtain.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the central nervous system (CNS) and kidneys are the two target organs of Hg 0 exposure (6). For the assessment of the level of human exposure to Hg 0 vapor, urine and serum total mercury (THg) concentrations are used as biomarkers (6,9,10). Many studies have shown a significant correlation between Hg concentrations in urine and serum and the Hg 0 concentration in air when exposure levels are high (6,(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…26 The paper suggests that when mercury exposure is at or below the ATSDR's 1-μg/m action level for mercury vapor relative to background levels of urinary mercury, 3 the contribution of mercury vapor exposure to measurable urine mercury levels may be negligible. Therefore, if mercury vapor was present in a child's environment at or below the residential action levels, it may not have been measurable in urine.…”
Section: Study Limitationsmentioning
confidence: 99%
“…The anonymous urines samples did not significantly differ from the enrolled population. Lastly, a recent article (26) suggests that the contribution of mercury vapor exposure to measurable urine mercury levels may be negligible relative to background levels of urinary mercury when the exposure is at or below the Agency for Toxic Substances and Disease Registry (ATSDR) action level for mercury vapor (1 μg/m3). If mercury vapor was present in a child's environment at or below the residential action levels, it may not have been measurable in urine.…”
Section: Limitationsmentioning
confidence: 99%